The Use of Figurative Language in Social Media Discourse during the 2024 Indonesian Presidential Election - Syamsuddin, Syamsuddin; Munfarida, Sakina (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2024)
This study examines the language styles used in netizens’ posts and comments on social media during the 2024 Presidential Election (Pilpres). Employing a qualitative descriptive approach, the research analyzes primary data in the form of written social media content and secondary data from relevant literature, utilizing orthographic and referential matching techniques. Among the 100 instances of hate speech identified, 30 distinct language styles were observed, with sarcasm (50 occurrences), hyperbole (30 occurrences), irony (20 occurrences), and rhetoric (10 occurrences) being the most prevalent. These language styles reflect expressions of dissatisfaction, anger, and criticism, while also capturing public attention. Sarcasm and irony effectively convey sharp satire, hyperbole introduces dramatic emphasis, and rhetoric evokes emotional reactions. The findings reveal that social media serves as a platform for political opinion contests, where language style functions as a strategic tool to construct narratives and influence public perception persuasively.